The relationship between certain body measurements and explosive power with jump shooting performance among basketball players at the College of Basic Education, University of Mosul (College of Basic Education Research Journal, 2026)
Despite numerous sources indicating the importance of anthropometric measurements and explosive power, physical attributes and strength have not received sufficient attention in the educational process implemented by teachers. These sources also point to the fact that the foundations of the educational and teaching process are based on an interaction between anthropometric measurements and physical attributes, particularly explosive power, which requires direct attention from instructors. Furthermore, despite the importance of scoring in basketball, a weakness in scoring is observed in many basketball games. The game ends with one team winning by a narrow margin, due to poor finishing. Therefore, the researchers decided to study this problem by examining the relationship between body measurements and explosive power as independent variables, and the skill performance in shooting. They aimed to analyze this relationship and demonstrate its role in the performance of the research sample, presenting it to instructors at both the student and player levels. This would enable them to adopt a sound scientific method for linking body measurements and explosive power to improve skill performance.
Keywords: Body measurements; explosive power; shooting performance